The Role of the Plantation and Animal Husbandry Office in Slaughterhouse Waste Management in Kolaka District, Kolaka Regency - Jannah, Nurfadilla Magfiratul (Teras Kampus, 2025)
This study aims to analyze the role of the Plantation and Livestock Service Office of Kolaka Regency in managing waste from slaughterhouses (RPH) in Kolaka District. Waste management at slaughterhouses is a crucial issue because it directly affects environmental cleanliness and public health in surrounding communities. This research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. The informants consist of officials from the Plantation and Livestock Office, slaughterhouse managers, and nearby residents. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the Plantation and Livestock Service Office plays a role as a facilitator by providing basic facilities and training in waste management, as a regulator by implementing technical standards for hygiene and sanitation, and as a catalyst by encouraging collaboration between the private sector and the community. However, waste management implementation remains suboptimal due to limited human resources, lack of waste treatment facilities, and low awareness among business actors regarding the importance of environmental sanitation. This study recommends strengthening the capacity of technical personnel, providing integrated waste treatment facilities, and improving coordination among related institutions to ensure more effective and sustainable slaughterhouse waste management.